Insect Repellants During Pregnancy in the Era of the Zika Virus. Issue 5 (November 2016) - Wylie, Blair J.; Hauptman, Marissa; Woolf, Alan D.; Goldman, Rose H.
Abstract : Health care providers must be equipped to provide appropriate advice to reproductive-aged patients for protection against the potentially devastating consequences of prenatal Zika virus exposure. The goal of this commentary is to summarize what is known about the safety and toxicity of N, N-diethyl-meta-toluamide (DEET) as a topical insect repellant and the pyrethroid permethrin for treatment of fabric, endorsed in the fight against Zika virus. Reviews assessing the safety and toxicity of DEET conducted by the U.S. Environmental Protection Agency and the Canadian Pest Management Regulatory Agency conclude that DEET has low acute toxicity and does not appear to pose a significant health concern to humans when used as directed. Some experimental animal and limited epidemiologic data suggest that prenatal pyrethroid exposure may adversely affect learning and behavior, but this level of evidence pales in comparison to the known risks of Zika virus to the fetal brain. The available evidence has led to the strong recommendation by the Centers for Disease Control and Prevention for use of these products by pregnant women as personal protection against mosquito bites in the fight against Zika virus infection. This message has been affirmed by our obstetrics and gynecology professional organizations. Because Zika virus is unlikely to be the last disease requiring vector control, those with environmental health expertise must continue to join with infectious disease specialists to communicate the potential vulnerability of our youngest (fetuses, infants, and young children) to vector-borne disease, both to the disease itself and to the strategies employed to mitigate the spread of such disease. Abstract : Based on available data for N, N-diethyl-meta-toluamide (DEET) and permethrin, health care providers and patients should have little reservation about recommended use during pregnancy for Zika virus prevention.